Poverty, food security and globalization : challenges for regional development - Ballayram (2005)
Articulates the links between, globalization, poverty and food security. Discusses the implications of these links within the context of Caribbean reality. Provides a perspective on how to shape and respond to globalization in order to enhance food security and alleviate poverty in the region.